New perspectives on Microsoft Word 97 : introductory - Zimmerman, Beverly B. (Course Technology, 1997)
This book is divided into seven parts: Creating a Document; Editing and Formating a Document; Creating a Multiple-Page Report; Desktop Publishing a Newsletter; Creating Styles, Outlines, Tables, and Table of Contents; Creating Form Letters and Mailing Labels; Integrating Word with Other Programs and with the World Wide Web.